PELATIHAN PENULISAN SASTRA KREATIF CRITA CEKAK BERBASIS KEARIFAN LOKAL KEBUDAYAAN JAWA BERSAMA MAHASISWA PROGRAM STUDI SEJARAH PERADABAN ISLAM KAMPUS UNIVERSITAS ISLAM NEGERI SAYYID ALI RAHMATULLAH TULUNGAGUNG - Nurul Baiti Rohmah; Uman Rejo (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2022)
The level of writing skills in Javanese and appreciation of Javanese literary works of second-semester students of the History of Islamic Civilization study program at the State Islamic University of Sayyid Ali Rahmatullah Tulungagung was not satisfactory. Therefore, training and mentoring activities for creative literary writing in honing written Javanese language skills need to be held. The main purpose of this service activity is to provide understanding and training in writing short stories of creative literature based on local wisdom of Javanese culture to second-semester students of the History of Islamic Civilization study program at the Sayyid Ali Rahmatullah State Islamic University Tulungagung campus. The method of carrying out activities is done online, namely for debriefing using Google Meet, while the products are sent via email. The debriefing will be held on October 15, 2021, and the writing of creative literary short stories has a duration of two weeks after the briefing. Based on the implementation of activities, it can be concluded as follows. The set of knowledge provided by the resource persons gave new nutrition and a positive impact on students to immediately write short stories based on local wisdom of Javanese culture. Short stories in the Javanese language produced by students are a form of honing students' writing skills in Javanese and a form of appreciation for Javanese literary works so that they remain sustainable and not be consumed by globalization. The short stories produced, after being read and selected carefully, will be published by a national publisher registered in IKAPI with an official ISBN. Tingkat ketrampilan menulis berbahasa Jawa dan mengapresiasi karya sastra Jawa mahasiswa semester dua program studi Sejarah Peradaban Islam di kampus Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung kurang memuaskan. Oleh karena itu, kegiatan pelatihan dan pendampingan penulisan sastra kreatif dalam mengasah kemahiran berbahasa Jawa tulis perlu diadakan. Tujuan utama kegiatan pengabdian ini adalah untuk memberikan pemahaman dan pelatihan penulisan sastra kreatif crita cekak berbasis kearifan lokal kebudayaan Jawa kepada mahasiswa semester dua program studi Sejarah Peradaban Islam di kampus Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung. Metode pelaksanaan kegiatan dilakukan secara daring, yakni untuk pembekalannya menggunakan Google Meet, sedangkan produknya dengan mengirim melalui email. Pelaksanaan pembekalan pada 15 Oktober 2021, dan penulisan sastra kreatif crita cekak berdurasi dua minggu setelah pembekalan. Berdasarkan pelaksanaan kegiatan, dapat disimpulkan sebagai berikut. Seperangkat ilmu pengetahuan yang diberikan narasumber memberi nutrisi baru dan dampak positif kepada mahasiswa untuk segera menulis crita cekak berbasis kearifan lokal kebudayaan Jawa. Crita cekak berbahasa Jawa yang diproduksi mahasiswa sebagai bentuk mengasah ketrampilan menulis berbahasa Jawa mahasiswa dan bentuk apesiasi terhadap karya sastra Jawa agar tetap lestari serta tidak termakan oleh arus globalisasi. Crita cekak yang diproduksi tersebut, setelah dibaca dan diseleksi dengan saksama, akan diterbitkan oleh penerbit nasional yang terdaftar dalam IKAPI dengan memiliki ISBN yang resmi.